Water sorption, solubility and surface roughness of resin surface sealants - Jaqueline Biazuz; Patrícia Zardo; Sinval Adalberto Rodrigues-Junior (Universidade Estadual de Campinas, 2015)
Surface sealants have been suggested as final glaze of the surface of composite restorations. However, little is known about bulk and surface properties of these materials aiming the long-term preservation of the surface integrity of these restorations. Aim: To evaluate the water sorption, solubility and surface roughness of commercial surface sealants for restorations. Methods: Five disc-shaped specimens (15 mm diameter X 1 mm high) were made from the surface sealants Natural Glaze (DFL) and Permaseal (Ultradent) and were light cured according to the manufacturer's instructions. The specimens were finished with 1500-grit SiC paper. Water sorption (WS) and solubility (SL) were assessed as recommended by the ISO 4049/2000 and were expressed in µg/mm3 . Surface roughness was evaluated before and after WS and SL, and was expressed in µm as R1 (before WS and SL) and R2 (after WS and SL). It was obtained from three parallel measurements along a 4mm length. Data were analyzed using t-test and paired t-test (α=0.05). Results: Water sorption and solubility of Natural Glaze were significantly lower than that of Permaseal (p<0.05). Degradation of the surface sealants did not affect significantly their surface roughness (p>0.05). Conclusions: Surface sealants used in composite restorations undergo hydrolytic degradation; however, this degradation seems not to interfere on surface roughness of these materials.